MARKETING IN THE MARKET OF EDUCATIONAL SERVICES (Conferencea, 2023)
This article discusses the objects of marketing in education, special attention is paid to specific features of educational services as the object of marketing. The functions and features of marketing in the market of educational services, as well as elements of the marketing mix, are outlined.